IMPROVEMENT OF PHOSPHATE FERTILIZATION METHOD IN WETLAND RICE - Cahyono, Ongko; Hartati, Sri (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2013)
The low efficiency of Phosphate fertilization on wetland rice may be overcame by using quickly dissolve P fertilizer. However, for soils containing high dissolve Fe, such as Alfisol and Oxisol, will induce the formation of Fe-P bonding. Therefore, to use the quickly dissolve P fertilizerÂ in such soils should be done by split application. The research aimed to assess better P fertilization method for wetland rice which used quickly dissolve P fertilizer given in split application. The research concluded that the application of quickly dissolve P fertilizer to Alfisol and Oxisol which was applied in split application by twice (0 and 30 days after planting) and three times (0, 15 and 30 days after planting) increased the eficiency of P fertilization in wetland rice.Â The split application of 75 kgs perhectare (one half of recommended dose) in Alfisol yielded dry seed as high as 6,374 kgs per hectare (at the twice application), 6,280 kgs per hectare (the three times application)c while the control treatment yielded as high as 6,027 kgs per hectare.Â In Oxisol the yield of rice was 8,200 kgs per hectare fo the control treatment, 8,027 kgs per hectare for the twice application and 8,440 kgs per hectare for the three time applications.